European merger control - Reynolds, Michael J. (Revista do IBRAC, 2025)
After over ten years of successful application of the Merger Regulation, the last 16 months have proved a far more controversial and challenging time for the Commission than the years that preceded them. In 2001, the Commission exercised its powers to block an unprecedented number of cases, although this should not be taken out of context. In 2001, there were 335 cases notified to the Commission of which 5 were prohibited. Furthermore, the Commission’s prohibitions in GE / Honeywell, Schneider / Legrand184 and Sidel/Tetra Laval185 provoked extensive comment on and criticism of the role of the Commission and its current practices. GE / Honeywell in particular raised particularly sensitive issues, given that the Commission’s prohibition related to an “all-American” merger which had been cleared by the US authorities.